2011
DOI: 10.1111/j.1600-0528.2011.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Two-Stage Rapid Estimate of Adult Literacy in Dentistry

Abstract: This work proposes a revision of the 30 item Rapid Estimate of Adult Literacy in Dentistry (REALD-30), into a more efficient and easier-to-use two-stage scale. Using a sample of 1,405 individuals (primarily women) enrolled in a Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), the present work utilizes principles of item response theory and multi-stage testing to revise the REALD-30 into a two-stage test of oral health literacy, named Two-Stage REALD or TS-REALD, which maximizes sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 16 publications
1
35
0
3
Order By: Relevance
“…The Spanish TOFHLA has a reported reliability of alpha = 0.98 (17). Past research has indicated strong associations for English-speaking samples between the TOFHLA and REALD-99 (9) and a two-stage REALD (18), suggesting the appropriateness of TOFHLA for testing convergent validity for the dental word recognition test.…”
Section: Methodsmentioning
confidence: 99%
“…The Spanish TOFHLA has a reported reliability of alpha = 0.98 (17). Past research has indicated strong associations for English-speaking samples between the TOFHLA and REALD-99 (9) and a two-stage REALD (18), suggesting the appropriateness of TOFHLA for testing convergent validity for the dental word recognition test.…”
Section: Methodsmentioning
confidence: 99%
“…In the testing of TS-REALD, 19 % were found to have low oral health literacy [23], while the corresponding figure for OHLI was only 3 % [29]. However, the authors of OHLI state that their study population were young and well educated adults who were frequent users of dental care, which may explain the low percentage of people with lower health literacy levels.…”
Section: Discussionmentioning
confidence: 68%
“…A revision of the REALD-30 has been published called the Two-Stage Rapid Estimate of Adult Literacy in Dentistry (TS-REALD) [23]. The TS-REALD format contains a routing test, which serves to define the respondent's initial literacy level, and three stage-two tests, which measure the respondent's health literacy score.…”
Section: Introductionmentioning
confidence: 99%
“…Among the measures that used IRT or Rasch modeling, most (n=9) [11, 2832, 36, 37] used data from estimated parameter values to strategically eliminate items that had low discrimination and items that targeted the same (difficulty) level of the underlying trait. When reviewing the range in trait levels across the items on measures where the b parameter estimate was reported, items ranged from b =‒6.34 to 2.06 [26].…”
Section: Limitations Of Validation Methodsmentioning
confidence: 99%